Coprecipitation of Organic Matter, Phosphate With Iron: Implications for Internal Loadings of Phosphorus in Algae-Dominated and Macrophyte-Dominated Lakes - Dai, JiaRu; Zhang, QiaoYing; Liu, JingJing; Wen, ShuaiLong; Zhang, YuFeng; He, Ding; Du, YingXun (Frontiers in Environmental Science, 2022)
Coprecipitation with iron (Fe) plays an essential role in the biogeochemical cycles of organic carbon (OC) and phosphorus (P) in lakes. The sources and composition of organic matter (OM) mediate its association with iron, which could thus influence the immobilization of phosphorus. In this study, water-soluble organic matter from the sediments of two typical states of shallow lakes, macrophyte-dominated zones (M-WSOM) and algae-dominated zones (A-WSOM), was extracted, and the ternary coprecipitation of WSOM, phosphate with Fe(III), was investigated. The ternary coprecipitation process was enhanced with increasing Fe(III) or decreasing pH value. It was found that pH of 6.5 was more favorable for coprecipitation than a pH of 7.5 or 8.5. At pH 6.5, the complexation between WSOM and Fe(III) occurred at the low Fe(III) inputs, while the coprecipitation of phosphate, WSOM with Fe(III) took place when Fe(III) inputs reached 40 μM. The presence of A-WSOM showed stronger inhibition on the coprecipitation of phosphate than that by M-WSOM. The formed ternary coprecipitates with A-WSOM had lower C/Fe ratios (0.13–2.78) than those with M-WSOM (1.28–4.05), which was because A-WSOM had lower aromaticity than M-WSOM. In addition, more functional groups in A-WSOM could complex with Fe(III), resulting in less immobilization of OC and P during the coprecipitation of A-WSOM, phosphate, and Fe(III). Our results demonstrated that in algae-dominated zones, more phosphorus remained soluble during the ternary coprecipitation, which could perform positive feedback on the growth of phytoplankton and provide a novel explanation for the difficulty in restoring eutrophic lakes.